Enabling Multi-User M-MIMO for High-Mobility Users with Predictor Antennas: A Deep Analysis Based on Experimental NLOS Measurements - Bjorsell, Joachim; Sternad, Mikael; Phan-Huy, Dinh-Thuy (IEEE transactions on vehicular technology, 2022)
Predictor antenna channel measurements from a 64-antenna base station are used to investigate the effects of channel aging on the precoder design for high-mobility users in a non-line-of-sight (NLOS) massive multiple-input multiple-output (M-MIMO) environment. The effects are evaluated in terms of received downlink (DL) signal-to-interference-and-noise ratio (SINR) and the corresponding ergodic capacity bound. A simulated velocity of 150 km/h is used with a carrier frequency of 2.18 GHz. Maximum ratio (MR) and a codebook-based precoders are used to evaluate single-user transmission; and zero-forcing (ZF), regularized zero-forcing (RZF), and minimum mean-squared error (MMSE) precoders are used to evaluate multi-user transmission with up to nine active users in a cell. Furthermore, predictor antenna predictions are evaluated as a mean of combating channel aging. It is also investigated how the predictor antenna can be used during data reception. Simulations show that outdated channel estimates significantly reduce the SINR and consequently the capacity for all investigated transmission techniques. Basic predictor antenna predictions outperform the use of outdated channel estimates for delays larger than 0.6 ms. In single-user transmission, channel prediction can improve the capacity by 6-14%. The gain from multi-user transmission typically disappears when using outdated channel estimates older than 1 ms. In contrast, the use of predictor antennas enables MIMO for these high-mobility users, which is demonstrated to increase the capacity bound by 100% compared to 1 ms old channel estimates.